Arqueología de la Segunda Guerra Mundial en Sudamérica : el asentamiento Nazi de Teyú Cuaré - Schávelzon, Daniel, (Archaeopress Archaeology, 2022)
This study reports on a remarkable discovery and a pioneering example of historical archaeology in Latin America: an unknown settlement was found nestled between rocky cliffs in the Argentinian jungle. Dated to between 1943-6, finds are characterised by exotic European luxuries, German coins and coins from the occupied countries of Western Europe.